Determination of new anthropometric cut-off values for obesity screening in Indonesian adults - Hastuti, J.; Kagawa, Masaharu; Byrne, N.; Hills, A. (HEC Press, 2017)
Background and Objectives: Body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), and waist-to-stature ratio (WSR) have increasingly been used as screening tools for obesity. However, optimal cut-off values may be different between populations. The current study determined the optimum cut-off values for BMI, WC, WHR, and WSR for obesity screening in Indonesian adults using receiver-operating characteristic (ROC) analysis. Methods and Study Design: Stature, body weight, waist and hip circumferences were measured on 600 Indonesians aged 18-65 years (males, n=292; females, n=308) and BMI, WHR, and WSR calculated. Percentage of body fat (%BF) was determined using the deuterium isotope (D 2 O) dilution technique. Some existing cut-off points for obesity determination were evaluated for sensitivity and specificity. Results: The existing cutoff values showed low sensitivity in our sample (between 18.4 and 71.1%) and new proposed cut-offs increased the sensitivity to reach 66.7 to 88.5%. The new cut-offs for BMI, WC, WHR, and WSR for determination of obesity were 21.9 (kg/m 2 ), 76.8 (cm), 0.86, and 0.48, respectively, for males and 23.6 (kg/m 2 ), 71.7 (cm), 0.77, and 0.47, respectively, for females. Conclusions: WC and WSR are the most predictive both for males and females, and therefore are considered as better screening tools for obesity in this population.